PARENTING IN EDUCATING CHILDREN IN ACCORDANCE WITH SUNNAH GUIDANCE - Islahuddin Islahuddin; Roslan Bin Yahya; Zulkifli Bin Awang Besar (Universitas Pendidikan Indonesia, 2021)
Education in a family with a muslim perspective is an education based on islamic religious guidance applied in the family that aims to shape children to become human beings who believe and fear Allah, as well as noble practices that include spiritual, ethical, ethical, moral, or understanding and experience of religious values in everyday life. This is one form of amar makruf nahi munkar in family life, namely by providing education to his daughter's son based on Islamic teachings. In getting to maturity, children need various processes played by their mothers and fathers in the family environment. The pattern of religious education in Islam is basically an example of the behavior of the Prophet Muhammad (peace be upon him) in building his family and friends, because everything done by the Prophet Muhammad (peace be upon him) is a form of manifestation of the content of the Qur'anic verse. As for the implementation, the Prophet Muhammad (peace be upon him) provided an opportunity for his followers in developing ways of education in children in the family as long as this method does not conflict with the principles of the implementation of education carried out by the Prophet Muhammad